The Empowerment of Women: A Vision for Human Security - Bijos, Leila (Revista Direitos Humanos Fundamentais, 2022)
The main objective of this paper is to analyze the insertion of women in education, new technologies of information and telecommunication, as well as in employment, breaking out the patriarchal structure especially in the Muslim world. It rests in the fact that in a relatively short time, women and their advocates have transformed the way-gendered-based violence is understood, and have promoted international documents and treaties that recognize women’s rights to live free of discrimination, violence and fundamentalists concepts. Theoretically, it focuses on the Beijing Platform for Action (1995) and the outcome of the Twenty-Third Special Session of the General Assembly (2000). Women’s experiences in Latin America, Asia and Africa are highlighted and show that the implementation of new paths for the insertion of women have changed some articles of the Civil Code, the High Council of Judicial Development for the revision of the Civil and Family Code, together with the Presidential Center for the Participation of Women for the implementation of the Project for the Reformation of the Women Comprehensive Legal and Judicial System so that women can step forward acquiring all the necessary abilities to insert themselves in a world free from the ravages of violence perpetrated by religious fundamentalists. This movement has been challenged by non-fundamentalist women who are claiming equality in society. The basic structures of society cannot be changed overnight, but each step in the ongoing effort to eradicate violence puts more pressure on those who condone the violence and education prohibitions and allow it to exist. This is the moment for a renewed commitment to build on the achievements of the last decade and find the resources for meaningful action. Without this commitment, much of what has been achieved may be lost. That would be a tragedy for all of us, since, as we have learned, women’s security is tied to global security.